2021
DOI: 10.3389/fevo.2021.759778
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Volatile Organic Compounds by Antennal Lamellae of a Scarab Beetle

Abstract: Chemoreceptive sensilla are abundantly distributed on antennal lamellae of scarab beetles. Olfactory reception by these sensory lamellae plays a major role in feeding behaviors and sexual communication of these beetles. A new electroantennogram (EAG) recording technique is here described for evaluation of electrophysiological responses of antennal lamellae of Pseudosymmachia flavescens to sex pheromones and host plant-related compounds. EAG responses were recorded simultaneously from each lamella and the close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…This differential odour sensitivity could potentially be attributed to the differential distribution of olfactory receptors responding to chemical cues. As an example, the middle lamella of the scarab beetle Pseudosymmachia flavescens (Coleoptera: Scarabaeidae: Melolonthinae) generated higher EAG responses than those of the proximal or distal lamella and the closed antennal club, which was found to have a significant correlation with the density of sensilla placodea in a previous study [27,62]. Single sensillum recordings (SSRs) have shown that olfactory neurons housed in densely arranged sensilla basiconica in G. auratus were sensitive to indole, skatole, phenol and p-cresol, while a separate group of olfactory cells responded specifically to butanone [28,48].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This differential odour sensitivity could potentially be attributed to the differential distribution of olfactory receptors responding to chemical cues. As an example, the middle lamella of the scarab beetle Pseudosymmachia flavescens (Coleoptera: Scarabaeidae: Melolonthinae) generated higher EAG responses than those of the proximal or distal lamella and the closed antennal club, which was found to have a significant correlation with the density of sensilla placodea in a previous study [27,62]. Single sensillum recordings (SSRs) have shown that olfactory neurons housed in densely arranged sensilla basiconica in G. auratus were sensitive to indole, skatole, phenol and p-cresol, while a separate group of olfactory cells responded specifically to butanone [28,48].…”
Section: Discussionmentioning
confidence: 83%
“…The EAG technique used in this study was similar to that previously described in the literature [60][61][62] and recordings were conducted only with female antennae (n = 3-11). Adult beetles were starved overnight and kept at 4 • C for 15 min to reduce their activity before dissection.…”
Section: Antennal Preparation and Electroantennogram Recordingsmentioning
confidence: 99%
“…The interaction between these volatile compounds and the insect olfactory system has been extensively studied. Detection involves the diffusion of volatile compounds into the sensilla located on the antenna, which has numerous pores [120,121]. These pores facilitate the absorption of VOCs by odorant-binding proteins (OBPs) within the sensilla, which are subsequently transferred to the odorant receptors (ORs) located on the sensory neurons [122].…”
Section: Functional Analysis Of Host Volatile Receptorsmentioning
confidence: 99%
“…The abundance of sensilla of various types appears to be related to several ecological factors including the dietary range (i.e., monophagous, oligophagous, polyphagous: Bland 1989; Chen et Malo et al 2004;Roh et al 2016). The inference that the sensitivity of an insect to its external environment depends on the abundance of sensilla (Bland 1989;Chapman 1989) is supported by observations using electro-physiological techniques such as electroantennography (EAG) and single sensillum recordings (SSRs) (Ochieng and Hansson 1999; Chen and Kang 2000; Malo et al 2004; Li et al 2021a). For example, the different phases of locusts show characteristic abundance of sensilla on their antenna.…”
Section: Introductionmentioning
confidence: 98%